2019
DOI: 10.3390/jcm8081227
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye Disease: A Review of Epidemiology in Taiwan, and its Clinical Treatment and Merits

Abstract: Dry eye disease (DED) has become common on a global scale in recent years. There is a wide prevalence of DED in different countries based on various ethnicities and environment. DED is a multifactorial ocular disorder. In addition to advanced age and gender, such factors as living at high altitude, smoking, pterygium, prolonged use of consumer electronics or overingesting of caffeine or multivitamins are considered to be the major risk factors of DED. We report the DED epidemiology in Taiwan firstly in this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 200 publications
(214 reference statements)
0
34
0
1
Order By: Relevance
“…The severity of bulbar redness can be objectively quantified via an automated and standardized image grading system. Moreover, meibography and ocular surface staining are two critical assessment for identifying evaporative dry eye [ 13 , 14 ] and ocular surface disease severity of dry eye [ 15 , 16 ], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of bulbar redness can be objectively quantified via an automated and standardized image grading system. Moreover, meibography and ocular surface staining are two critical assessment for identifying evaporative dry eye [ 13 , 14 ] and ocular surface disease severity of dry eye [ 15 , 16 ], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Katılımcıların yaş ortalaması 30.06 ± 4.794 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) yıl idi. Katılımcıların bilgisayar kullanım süresi ortalama 10.15 ± 3.040 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) saat/gün idi. Ortalama OYHİ skoru 31.0742 ± 15.05892 (8.3-75) idi.…”
Section: öZetunclassified
“…The DED, especially affecting middle-aged or older individuals, is one of the most common ocular surface diseases on a global scale in recent years [6][7][8] . The DED has been a major public health problem in older people for years, especially prolonged use of electronic devices in modern society has posed a challenge for DED in recent years 9,10 . The DED, a multifactorial disorder of tear film and ocular surface, results in increased osmolarity and instability of the tear film, the discomfort of eye, visual impairment and potential damage and inflammation of the ocular surface [6][7][8]11 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the risk factors for DES, women have repeatedly been found to be at increased risk of DES compared with men [ 10 , 12 , 13 , 14 , 15 ]. A Taiwanese nationwide dataset (2001–2015) also showed that females had a significantly higher annual incidence rate of DES than males [ 16 ]. Furthermore, previous studies have indicated that postmenopausal women and women receiving hormone therapy have more severe cases of dry eye [ 13 , 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%